Prognostic Observational Analysis of BMI, Leptin, and Adiponectin in Children With Acute Lymphocytic Leukemia Undergoing Remission-Induction Chemotherapy - Sun, Jing; Zhang, Ru; Tang, Jianjun; Wu, Xuedong; Zhu, Lu; Huang, Haiying; Chen, Huimin; Xiao, Minhua; Luo, Hongfeng; Zheng, Haiqing; Chen, Jiaqi (Frontiers in Pediatrics, 2022)
Background: Childhood acute lymphoblastic leukemia (ALL) survivors often have adverse effects after treatment, such as an increased risk of obesity. Obesity has been associated with reduced survival. Objective: We investigated the relationship between obesity, adipocytokine levels, and ALL short-term outcomes. Methods: Weight and height were measured, and body mass index (BMI) was calculated at diagnosis and discharge. Leptin and Adiponectin levels and Minimal Residual Disease (MRD) were measured before therapy, at days 19 and the end of remission-induction therapy (days 46). The relationship between BMI, adipocytokine levels, and MRD was then determined. Results: Compared to the normal BMI group, children with an abnormal increase in BMI had an increase in MRD at day 19 and 46 (P=0.04, P=0.008), and showed a positive correlation (P=0.014). Positive correlations between weight, hip circumference at diagnosis and at day19, and MRD at day 46 were found; suggesting fat concentric distribution also affected ALL outcomes. A higher BMI was also associated with a significant increase in Leptin levels at diagnosis. Leptin resistance should be considered in ALL children with high BMI. Conclusion: BMI affects the outcome of ALL patients. Early interventions such as regular BMI monitoring, and dietary assessments should be initiated during remission-induction chemotherapy.